2013
DOI: 10.3141/2393-18
|View full text |Cite
|
Sign up to set email alerts
|

Do All Roadway Users Want the Same Things?

Abstract: This paper presents findings from a recent study on roadway design preferences among pedestrians, drivers, bicyclists, and public transit users along a major urban corridor in the East San Francisco Bay Area. Sponsored by the California DOT, the research focused on exploring design preferences that could increase perceived traffic safety, walkability, bikability, and economic vitality along urban arterials.Results from an intercept survey showed that all user groups desire similar roadway design features along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In spite of the few inconclusive studies cited in the paragraph above, stated-preference surveys of cyclists and non-cyclists typically showed that cyclists preferred and felt safer on bike lanes compared to cycling in traffic (Akar & Clifton, 2009;Antonakos, 1994;Fishman, Washington, Haworth, & Watson, 2015;Landis, Vattikuti, & Brannick, 1998;Sanders & Cooper, 2013;Sener et al, 2009a). Several studies describe other types of bike lanes, such as colored bike lanes, shared bus and bike lanes, advisory bike lanes using dashed lines on roadways to dedicate space for bicycles, extra-wide lanes to accommodate cyclist's lateral movement when cycling uphill, or contra-flow bike lanes on one-way roads for cars (Buehler & Handy, 2008;Furth, 2012;Pucher & Buehler, 2008), but they did not isolate the impact of these facilities on cycling levels or cyclist perceptions.…”
Section: Separate Facilities: Bike Lanes Cycle Tracks and Bike Pathsmentioning
confidence: 95%
“…In spite of the few inconclusive studies cited in the paragraph above, stated-preference surveys of cyclists and non-cyclists typically showed that cyclists preferred and felt safer on bike lanes compared to cycling in traffic (Akar & Clifton, 2009;Antonakos, 1994;Fishman, Washington, Haworth, & Watson, 2015;Landis, Vattikuti, & Brannick, 1998;Sanders & Cooper, 2013;Sener et al, 2009a). Several studies describe other types of bike lanes, such as colored bike lanes, shared bus and bike lanes, advisory bike lanes using dashed lines on roadways to dedicate space for bicycles, extra-wide lanes to accommodate cyclist's lateral movement when cycling uphill, or contra-flow bike lanes on one-way roads for cars (Buehler & Handy, 2008;Furth, 2012;Pucher & Buehler, 2008), but they did not isolate the impact of these facilities on cycling levels or cyclist perceptions.…”
Section: Separate Facilities: Bike Lanes Cycle Tracks and Bike Pathsmentioning
confidence: 95%
“…Such objective measures have been supported in Geographic Information Systems [30][31], multi-criteria analysis [25,32], virtual technologies [29,33], Web-based services, such as WalkScore, among others. Subjective measures have been supported on qualitative assessments based on stated preferences and individual perceptions usually collected through questionnaires or by consulting expert panels [34]. Walkability has been analysed by assessing different criteria.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This raises the specter of walkable gentrification, where increasingly popular location-efficient walkable neighborhoods become affordable to fewer people ( 40 ). Complete Streets are another manifestation of public demand for more widely shared benefits of urban efficiency and walkability ( 41 ).…”
Section: Walkability and Walking: Environment And Behaviormentioning
confidence: 99%